2020
DOI: 10.5694/mja2.50583
|View full text |Cite
|
Sign up to set email alerts
|

The carbon footprint of pathology testing

Abstract: Objectives:To estimate the carbon footprint of five common hospital pathology tests: full blood examination; urea and electrolyte levels; coagulation profile; C-reactive protein concentration; and arterial blood gases.Design, setting: Prospective life cycle assessment of five pathology tests in two university-affiliated health services in Melbourne. We included all consumables and associated waste for venepuncture and laboratory analyses, and electricity and water use for laboratory analyses.Main outcome measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 22 publications
0
69
0
Order By: Relevance
“…Process-based LCAs arrive at an environmental cost for an item or activity based upon directly measured material inputs and using LCI databases that report emissions associated with those materials. For example, recent process-based healthcare analyses of blood pressure cuffs, 75 and pathology tests 76 measured the weights, compositions, and actual use of such items in detail. Process-based LCAs tend to focus on a small, targeted, easily defined product or process and are excellent for making comparisons (e.g.…”
Section: Life Cycle Assessmentsmentioning
confidence: 99%
“…Process-based LCAs arrive at an environmental cost for an item or activity based upon directly measured material inputs and using LCI databases that report emissions associated with those materials. For example, recent process-based healthcare analyses of blood pressure cuffs, 75 and pathology tests 76 measured the weights, compositions, and actual use of such items in detail. Process-based LCAs tend to focus on a small, targeted, easily defined product or process and are excellent for making comparisons (e.g.…”
Section: Life Cycle Assessmentsmentioning
confidence: 99%
“…To the Editor : The Royal College of Pathologists of Australasia (RCPA) is concerned with some of the conclusions drawn in the article by McAlister and colleagues 1. We support the suggestion that there are opportunities for reducing waste and carbon dioxide emissions in pathology laboratories and, with the RCPA Quality Assurance Programs, we encourage laboratories to reduce their environmental impact whenever possible.…”
mentioning
confidence: 78%
“…Reducing carbon emissions by health care requires clear understanding of current emission levels and their sources. McAlister and his co‐authors describe their assessment of the carbon footprint of five pathology tests commonly performed in hospitals . They found that sample collection, because of the consumables involved, is the most carbon‐intense component of a pathology test.…”
mentioning
confidence: 99%